Production Constraints of Animal Based Farming Enterprises in Coastal India (Indian Journal of Extension Education, 2010)
The present study envisaged to assess and analyse the various constraints of individual farm enterprises in coastal Tamil Nadu. The ranking was done by the farmers based on the importance or severity of the problems in eight coastal villages using Rank Based Quotient (RBQ) method. Low milk price, diseases, decreasing common grazing land in livestock production; disease and predators in poultry and lack of government support, wide price fluctuations in fisheries were ranked by farmers as major problems in individual enterprises. The major constraints in adopting integrated farming system were found to be heavy investment in the initial stage, lack of markets for the produce from different enterprises, labour unavailability and its high cost and lack of infrastructure in addition to scattered land holdings of farmers.